2022
DOI: 10.3389/fnut.2022.991524
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the protective roles of alpha-lipoic acid supplementation on nanomaterial-induced toxicity: A meta-analysis of in vitro and in vivo studies

Abstract: Extensive exposure to nanomaterials causes oxidative stress and inflammation in various organs and leads to an increased risk of adverse health outcomes; therefore, how to prevent the toxic effects are of great concern to human. Alpha-lipoic acid (ALA) has anti-oxidant and anti-inflammatory activities, suggesting it may be effective to prevent nanomaterial-induced toxicity. However, the results obtained in individual studies remained controversial. We aimed to comprehensively evaluate the effects of ALA supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…Moreover, for some supplements, it has been shown that they can have protective effects. Thus, for example, basic fibroblast growth factor (bFGF) is protective against Ab1–42-induced toxicity [ 2 ], while alpha-lipoic acid supplementation was shown to provide protective effects against nanomaterial-induced toxicity [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for some supplements, it has been shown that they can have protective effects. Thus, for example, basic fibroblast growth factor (bFGF) is protective against Ab1–42-induced toxicity [ 2 ], while alpha-lipoic acid supplementation was shown to provide protective effects against nanomaterial-induced toxicity [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most important is LA which has anti-oxidant and anti-inflammatory activities. This acid antagonizes nanomaterials, inducing inflammatory responses and oxidative damage toxicity [ 24 ]. This is mainly through increased GSH, decreased IL-6, and chelation of metal ions [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…This acid antagonizes nanomaterials, inducing inflammatory responses and oxidative damage toxicity [ 24 ]. This is mainly through increased GSH, decreased IL-6, and chelation of metal ions [ 24 ]. Therefore, FANC, which we used in this study, carries LA and may prevent the toxicity induced by gold nanoclusters.…”
Section: Introductionmentioning
confidence: 99%